GAYA KOMUNIKASI PEREMPUAN PEMIMPIN DI INDUSTRI PERHOTELAN - Rinaldi, Aldi; Ramadhani, Beby (Penerbit Lafadz Jaya, 2024)
This study aims to explore the characteristics of women's leadership in the hospitality industry, with a focus on female executives at Industri Perhotelan. The research method used is direct interviews with eight female executives, using a semi-structured interview guide instrument. The results of this study provide an overview that women's leadership in the hospitality industry encompasses not only professional aspects but also personal qualities such as courage, honesty, and creativity. Moreover, female leaders at Industri Perhotelan tend to adopt a democratic leadership style that promotes collaboration and team participation.